Short Communication: Prevalence and risk factors of soil-transmitted helminth infection among farmers in Gelgel Village, Klungkung District, Bali, Indonesia - budiapsari putu indah; ANAK AGUNG GEDE INDRANINGRAT; HENY ARWATI; YOES PRIJATNA DACHLAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Apsari PIB, Indraningrat AAG, Arwati H, Dachlan YP. 2020. Short Communication: Prevalence and risk factors of soil-transmitted helminth infection among farmers in Gelgel Village, Klungkung District, Bali, Indonesia. Biodiversitas 21: 1535-1540. Soil-transmitted helminths infection remains a problem in tropical and subtropical regions worldwide. Indonesia is one of the tropical countries with a high prevalence of STH infection in children and high-risk population such as farmers. This study aimed to assess the prevalence and risk factors of STH infection from farmers. STH infection was diagnosed by Kato-Katz modified technique, while risk factors relevant to STH infection were assessed by a questionnaire. Data were analyzed by logistic regression and multiple regression test. A total of 162 fecal-samples and questionnaires were obtained from 250 participants. Twenty-two subjects (13.5%) were positive, and 140 subjects (86.5%) were negative for STH infection giving the prevalence rate of 13.5% among farmers. Several significant risk factors for STH infection were age, gender, level of study, income, eating fresh unwashed vegetable, hand washing without soap, defecation site, without wearing hand gloves and protective cloth, bare walking foot, and the use of synthetic fertilizer. So we can conclude that personal hygiene factors were the most contributed factors for STH infection.